1979
DOI: 10.3102/00346543049003459
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Type and Combination of Feedback upon Conceptual Learning by Children: Implications for Research in Academic Learning

Abstract: Laboratory research was reviewed that compared the effects of various types (verbal, symbolic, tangible) and combinations (right-wrong, right-blank, wrong-blank) of feedback upon children's conceptual learning. This research was evaluated in terms of theories involving reinforcement, motivation, and information-processing interpretations. In general, the findings have been consistent in two respects: (I) Verbal and symbolic feedback produce more rapid acquisition than does tangible feedback. (2) The wrong-b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
10
0

Year Published

1981
1981
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(12 citation statements)
references
References 70 publications
2
10
0
Order By: Relevance
“…However, children appear to process negative versus positive feedback differently from adults (Eppinger et al 2009); for example, adults and 11-13 year-olds learned more quickly from negative than positive feedback, whereas 8-9 year olds learned most from positive feedback (Van Duijvenvoorde et al 2008). Multiple try and interactive tutoring feedback incorporate both negative and positive feedback components, the combination of which has yielded mixed results in children (Barringer and Gholson 1979). It is possible that providing a different kind of simple feedback -e.g., only showing the correct response -would be even more effective for children and this should be examined in future studies.…”
Section: Interactive Tutoring Feedback Is More Effective Than Multiplmentioning
confidence: 99%
“…However, children appear to process negative versus positive feedback differently from adults (Eppinger et al 2009); for example, adults and 11-13 year-olds learned more quickly from negative than positive feedback, whereas 8-9 year olds learned most from positive feedback (Van Duijvenvoorde et al 2008). Multiple try and interactive tutoring feedback incorporate both negative and positive feedback components, the combination of which has yielded mixed results in children (Barringer and Gholson 1979). It is possible that providing a different kind of simple feedback -e.g., only showing the correct response -would be even more effective for children and this should be examined in future studies.…”
Section: Interactive Tutoring Feedback Is More Effective Than Multiplmentioning
confidence: 99%
“…Concept formation involves learning to categorize individual things as instances of a common type, which, in turn, involves identifying salient properties of the category. Concept identification involves recognizing what concept is relevant to performing some mental task (see the reviews in Marshall, 1965, andBarringer &Gholson, 1979). A simple example of concept formation would be learning to correctly differentiate everything that is a triangle from everything that is not.…”
mentioning
confidence: 99%
“…157-160, for discussion). The various studies reviewed in Marshall (1965) and Barringer and Gholson (1979) examined variables such as the timing of feedback (immediate vs. delayed), the form of feedback (reward vs. punishment, verbal vs. monetary rewards, and so on), and the nature of feedback (positive vs. negative feedback). Positive feedback confirms in some way the correctness of the original behavior.…”
mentioning
confidence: 99%
“…Feedback given later was found to be more effective than immediate feedback in regular teaching and learning processes (Kulik & Kulik, 1988) as well as in a computer-aided instruction context (Clariana, Wagner, & Murphy, 2000). Barringer and Gholson (1979) found that symbolic and verbal feedbacks were more effective compared to rewards given in a computer-based learning environment. They also found feedbacks given for incorrect answers were more effective than the ones given for correct answers.…”
Section: Introductionmentioning
confidence: 89%